Short selling and economic policy uncertainty - CAO, Xiaping (Institutional Knowledge at Singapore Management University, 2017)
We study the trading behavior of short sellers in the presence of economic policy uncertainty (EPU). Daily short selling activity at either the aggregate level or the individual stock level is increasing in the EPU index (Baker, Bloom and Davis, 2016). EPU has great explanatory power for short trading. Cross-sectional tests show that the increase in short interest under high political uncertainty is from shorting stocks characterized by higher mispricing, greater policy sensitivity, higher illiquidity, greater volatility or analyst dispersion. Short sellers earn abnormal profits by trading on public information related to EPU.